Effect of synthesis temperature on crystal structure, optical and magnetic properties of SmCuO3-δ ceramic phosphor - Yadav S.; Kumar D.; Singh A.K. (My University, 2025)
Effect of synthesis temperature on crystal structure, optical and magnetic properties of SmCuO3-δ ceramic phosphor is investigated in this work. The SmCuO3-δ ceramic has been synthesized using a sol-gel method. Rietveld analysis reveals that SmCuO3-δ ceramic crystallizes into coexisting tetragonal (I4/mmm) and monoclinic (C2/c) crystal structures. The phase fraction of the tetragonal and monoclinic phases strongly depends on the synthesis temperature. The crystallite size and particle size increase with increasing calcination temperature. The X-ray photoelectron spectroscopic spectra reveal the presence of (Cu2+, Cu3+) and (Sm2+, Sm3+) ions alongwith the oxygen vacancy centres in the phosphor. The SmCuO3-δ ceramic shows multiple magnetic phase transitions. The FTIR spectra show the presence of vibrational bands due to Cu-O and Sm-O groups. The optical band gap of the SmCuO3-δ phosphor decreases with an increase in calcination temperature and crystallite size. The photoluminescence excitation spectra show the peaks at 363, 402, 505 and 542 nm at the fixed emission wavelength of 609 nm, whereas the photoluminescence emission spectra contain peaks at 465, 515 and 609 nm at the fixed excitation wavelength of 402 nm. The photoluminescence emission intensity of the sample increases with the rising calcination temperature upto 900 °C and finally, it quenches at 1000 °C. Therefore, the SmCuO3-δ ceramic phosphor may be useful for solid state lighting, LEDs and magnetic devices. © 2023 Elsevier Ltd